EVALUATION OF PAIN SYNDROME IN PATIENTS WITH ENDOMETRIOSIS-ASSOCIATED PELVIC PAIN CAUSED BY EXTERNAL GENITAL ENDOMETRIOSIS - M. R. Orazov; E. N. Nosenko; M. B. Khamoshina; L. K. Barsegyan; E. S. Tokaeva; Ya. R. Zakirova (Акушерство, гинекология и репродукция)
The aim of the study was to evaluate the severity of pain syndrome and depression syndrome in women with endometriosis- associated pelvic pain. Materials and methods. The study included 100 women of reproductive age with external genital endometriosis. The study group consisted of 60 patients with pelvic pain associated with external genital endometriosis; the control group consisted of 40 women with external genital endometriosis without pain. The pelvic pain was ranked using the Visual Analog Scale (VAS); the level of depression was evaluated using the Beck scale; the anxiety was rated according to the Spielberger-Khanin questionnaire. Results. Among the 60 women in the study group, 20 patients (33.3%) had severe pain, 25 women (41.6%) had moderately severe pain, and 15 women (25.1%) had mild pain. The occurrence of depressive disorders in women with endometriosis-associated pelvic pain was 64%. Conclusion. The results suggest that the psycho-emotional status of women with external genital endometriosis-associated pelvic pain is dominated by high level of depression and anxiety, which significantly downgrades their quality of life.